2017
DOI: 10.15625/2525-2321.2017-00481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyamine 70000 (BT70) on the zinc plating process in the non-cyanide alkaline plating bath

Abstract: The effect of polyamine having molecular weight 70,000u (BT70) in the non-cyanide alkaline plating bath on the morphological zinc electrodeposited coating was investigated. The obtained results from the reflectance of electrodeposited zinc coating by a suitable range of electro-current density and SEM images showed that BT70 had effect on the zinc plating in comparison with the zinc deposits from plating bath without BT70. The electrodeposited coating surface was rough and poor adhesion. However, adding BT70 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…8 and Tab. 1 are Hull cell patterns obtained from the alkaline zinc plating solutions including Bt700 from reference [7]. In the case of same number of substituents of polyamines, the brightness (BN) and semi-bright ranges (SBR) of the deposits using polyamines with low molecular weight Bt18 (BN = 14 and SBR < 3 A/dm 2 ) and Q7-20 (BN = 4.6 and SBR < 2 A/dm 2 ) were poorer than those of the deposits using polyamines with high molecular weight Bt700 (BN = 56.7 and SBR < 10 A/dm 2 ) and Q7-700 (BN = 15.3 and SBR < 4.5 A/dm 2 ), respectively.…”
Section: Effect Of the Number Of Substituents And Molecular Weight Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…8 and Tab. 1 are Hull cell patterns obtained from the alkaline zinc plating solutions including Bt700 from reference [7]. In the case of same number of substituents of polyamines, the brightness (BN) and semi-bright ranges (SBR) of the deposits using polyamines with low molecular weight Bt18 (BN = 14 and SBR < 3 A/dm 2 ) and Q7-20 (BN = 4.6 and SBR < 2 A/dm 2 ) were poorer than those of the deposits using polyamines with high molecular weight Bt700 (BN = 56.7 and SBR < 10 A/dm 2 ) and Q7-700 (BN = 15.3 and SBR < 4.5 A/dm 2 ), respectively.…”
Section: Effect Of the Number Of Substituents And Molecular Weight Ofmentioning
confidence: 99%
“…In Viet Nam, nowadays, additive systems for the noncyanide alkaline bath used in the industries are all imported, and no published documents of the additives have been found. In our previous research, we have investigated the effects of molecular weight of polyamines on the non-cyanide alkaline zinc plating process [7]. The results showed that molecular weight of polyamines had strong effects on the non-cyanide alkaline zinc plating process in which the heavier molecular weight, the stronger effects.…”
Section: Introductionmentioning
confidence: 99%